Weight Loss App Descriptors in App Stores: A Qualitative Analysis of the Spanish Market - Lara Martin-Vicario; Javier Bustos Díaz; Ruben Nicolas-Sans (Human Behavior and Emerging Technologies)
Mobile applications for weight loss have arisen the interest of private companies and developers, who have put great efforts on the development of this kind of apps. This topic has attracted the interest of the scientific community, both in terms of usability and design. Two main issues have, however, arisen: firstly, research focus has been on the apps themselves, but little attention has been paid to how they are presented in the application stores, and secondly, current literature focuses solely on applications in English. The study objective is to observe how the most popular weight loss applications for the Spanish market are presented in the stores. Using thematic analysis, this study is aimed at discovering the themes featured in the store descriptions and to observe what functionalities are highlighted in these descriptions. The initial sample was based on 247 weight loss applications, which after revision was reduced to 7 applications. Our results show that they focused on efficacy, speed, and, to a much lesser degree, safety in weight loss. Among the main results, we found that app descriptors analyzed did not employ a scientific language and demonstrate technical expertise, or user testimonials. On the other hand, the claims made by the apps about weight loss were mainly based on effectiveness. This sometimes included the concept of quick results and, to a lesser extent, health and safety. Lastly, we observed that there is room for improvement in the linguistic and cultural adaptation of the texts of these application descriptions. Regarding the study limitations, the reduced number of the sample is because our study focuses on applications with features that follow international weight loss guidelines, which most of them did not follow.